Diversity of Frankia strains associated to Myrica gale in Western Europe: impact of host plant ( Myrica vs. Alnus ) and of edaphic factors - Valérie Huguet; Max Mergeay; Emilio Cervantes; Maria P. Fernandez (Environmental Microbiology, 2004)
Summary Myricaceae can be nodulated by a variety of Frankia strains isolated from other actinorhizal families. Consequently, the genus Myrica has been considered to have low specificity with respect to microsymbiont taxa. In contrast to controlled studies of Myrica infectious capacity, field studies in North America have indicated that M. gale symbionts belong to the genetic group of Alnus ‐infective strains. Myrica gale is the most widely distributed species in the genus so this study focused on describing the genetic diversity of M. gale ‐nodulating strains from 10 sites in Western Europe across a range of edaphic conditions. When possible, the specificity of M. gale ‐infective strains was compared with that of Alnus ‐infective strains from the same sites. Nodular strains from Belgium, France and Spain were characterized using PCR‐RFLP of rrs gene and 16S‐23S IGS. rrs ‐RFLP patterns showed a high level of homogeneity among European strains with one dominant genotype. IGS‐RFLP patterns revealed the largest inter and intrasite diversity in France. In Belgium, Frankia strains were found to occur in two groups according to soil pH and organic matter characteristics of the sites. European M. gale ‐infective strains were genetically different from European Alnus and North American M. gale ‐infective strains indicating the possibility of different pathways of co‐evolution among geographically isolated populations.